Aspek Hukum Keselamatan Penerbangan di Indonesia - Niru Anita Sinaga (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
Aviation as part of the national transportation system has an important role in people's lives, therefore the implementation must be arranged in an integrated national transportation system by integrating and dynamizing aviation infrastructure and facilities. The purpose of the flight operation is to realize an orderly, regularly, safe, secure, comfortable flight, etc. This is in accordance with the motto that is generally accepted in the aviation world, that is 3S+1C: Safety, security, services and compliance to rules. In order to support the smooth running of flight activities, it is required to comply with applicable regulations, including: Article 44 of the 1944 Chicago Convention, International Civil Aviation Organization (ICAO), Aviation Law, Government Regulations, Regulations and Decrees of the Minister of Transportation and other Implementing Regulations. There are various factors that affect flight safety performance that can be used as a joint evaluation material for the achievement of flight safety services in accordance with national and international regulations. This study discusses: How is the regulation and implementation of aviation safety policies in Indonesia? This type of research is normative legal research (juridical normative), using secondary data obtained from primary, secondary, and tertiary legal sources.